Improving the Preparedness of Housewives to Deal with the Dynamics of the COVID-19 Pandemic Situation - Indri Seta Septadina; Iche Andriyani Liberty; Emma Novita; Eddy Roflin; Pariyana; Abdusallam; Syifa Inanta Mulia Nasution (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
COVID-19 (Coronavirus Disease-19) caused by the SARS-CoV-2 virus is known to attack all ages. Not only adults, it can also be dangerous for the elderly and children. On the other hand, offline schools have been planned to be carried out. Therefore, it is important for parents who have school-age children to know the impacts and situations that occur during the COVID-19 pandemic. The target subjects for this community service activity are 27 people who live in the Jakabaring, Palembang. This community service activity resulted in an increase in knowledge about the dynamics of the COVID-19 pandemic situation and the importance of health protocols to protect families, especially if the children attend offline school, as well as conducting periodic visits to see the development of the consistency of people's attitudes and behavior. This community service activity is also carried out in order to increase the participation of the community in the area to become the successor of information regarding the dynamics of the COVID-19 pandemic situation and the importance of health protocols to protect families, especially if the children who will attend offline school.